Insights into Two Novel Orthopalladated Chromophores with Antimicrobial Activity against Escherichia coli - Rosita Diana; Francesco Silvio Gentile; Antonio Carella; Luigi Di Costanzo; Barbara Panunzi (Molecules, 2022)
Advanced chromophoric tools, besides being biologically active, need to meet the expectations of the technological demands including stability, colour retention, and proper solubility for their target. Many coordination compounds of conjugated ligands are antibacterial dyes, able to combine a strong dyeing performance with a useful biological activity. Specifically, palladium (II) complexes of Schiff base ligands are known for their relevant activity against common bacteria. In this article, we report the synthesis and comprehensive experimental and theoretical characterization of two novel Pd(II) chromophore complexes obtained from a cyclopalladated Schiff base as two different chelating azo dyes. The antibacterial response of these two novel complexes was tested against the ubiquitous Escherichia coli bacterium in an aqueous medium and revealed a noteworthy antimicrobial activity, higher than when compared with their uncoordinated biologically active ligands.